Adult Education to Become Citizen. An Experience from Southern Europe - Emilio Lucio-Villegas; Antonio Fragoso (Adult Education Research Conference, 2010)
In this paper, we present a reflection on experiences with adult education and participation. We consider citizenship as something connected to social justice and to social inclusion.